Inovasi Pelatihan Pembuatan Pestisida Nabati Berbasis Bahan Lokal dan Rempah Dapur untuk Mengendalikan Hama di Desa Pejagatan - Panggih Pangestu; Yulistiana Irawati; Muhammad Adi Sampurno; Ummatullatifah Ummatullatifah; Resi Kurnia Sari; Rosy Solekhati; Ani Fitrotul Izah; Emilia Wahyu Utami; Rahma Ida Dwi Cahyantika; Tirto Waluyo; Anti Isnaningsih (Institut Teknologi dan Bisnis Semarang, 2026)
Excessive use of synthetic chemical pesticides in Pejagatan Village, Kutowinangun District, Kebumen Regency, poses severe risks to environmental sustainability and public health. To address this issue, the UMNU Kebumen KKN team conducted a community empowerment program focused on producing eco-friendly botanical pesticides. Held on Sunday, August 2, 2026, at 20:00 WIB at the Pejagatan Village Hall, the activity engaged members from all five active local farmers' groups (Kelompok Tani). The training introduced an enhanced formulation incorporating soursop leaves, papaya leaves, tobacco, cream detergent, as well as easily accessible kitchen spices/rhizomes (ginger, turmeric, kaempferia galanga, curcuma aeruginosa, curcuma heyneana, galangal, calamus, and cassumunar ginger), garlic, clove oil, baking soda, neem leaf powder, and Nitrobacter. The addition of kitchen spices significantly intensified the pungent aroma of the mixture, thereby accelerating pest eradication. The program stages included material presentation via PowerPoint and brochures, an active Q&A session with local farmers, and hands-on practice using 15-liter Le Minerale gallons. Furthermore, participants received ready-to-use botanical pesticide samples pre-made by the KKN team. The physical evaluation after 24-hour fermentation confirmed an optimal dark, pungent, and homogeneous solution. This program successfully transferred practical technology, offering an effective, economical, and sustainable plant protection alternative.